Evaluation and Comparison between three different crude oils via chemical composition and physical properties including carbon distribution - Abdalla, Gashaw L.; Karim, Abdulsalam R.; Hamasalh, Luqman Omar (Sulaimani Journal for Pure and Applied Sciences, 2023)
For vast decision-making during the production process, knowing the physicochemical properties of petroleum and petroleum fractions is of major significance. Different types of crude oils from the Kurdistan Region and Iraq, namely (S for Sarqalla, K for Kirkuk, and B for Bardarash), have been compared, evaluated, and physicochemically characterized. American Society for Testing and Materials (ASTM), Universal Oil Production (UOP), and Institute of Petroleum (IP) standard test methods were used to estimate (density (Kg/m3 ), API gravity, viscosity (cSt), salt content (ppm), H2S content (ppm), flash point ( oC), pour point ( oC), sulphur (wt%), Reid vapor pressure (psi), asphaltene (wt%), and ash content (wt%)) to know the complexity of crude oils. Crude oils were fractionated into fractions based on their true boiling point via carbon distribution, including the paraffin, naphthenic, and aromatic (PNA) composition of their fractions through the refractive index-density-Molecular weight (n-d-M) method using a standard test method of ASTM D 3238, as well as the determination of metal elements in crude oils by inductively coupled plasma optical emission spectroscopy (ICP-OES). Afterward, Fourier transform infrared (FT-IR) spectroscopy was used for the characterization of precipitated asphaltene in crude oils and their residues (+270 oC). It was found that they have very similar chemical structures.
Keywords: Petroleum Kurdistan Region and Iraq Physicochemical properties Asphaltene ICPOESASTM D 3238